Neoadjuvant Chemotherapy in Elderly Patients With Upper Tract Urothelial Cancer: Oncologic Outcomes From a Multicenter Study - Grossmann, Nico C; Pradere, Benjamin; D'Andrea, David; Schuettfort, Victor M; Mori, Keiichiro; Rajwa, Pawel; Quhal, Fahad; Laukhtina, Ekaterina; Katayama, Satoshi; Fankhauser, Christian D; Xylinas, Evanguelos; Margulis, Vitaly; et al. (Clinical genitourinary cancer, 2022)
INTRODUCTION: Although upper tract urothelial carcinoma (UTUC) is more common in the elderly, outcomes of neoadjuvant chemotherapy (NAC) in this population have never been explored. The objective of the study was to assess the impact of NAC on pathologic response and oncological outcomes stratified by age. PATIENTS AND METHODS: This multicenter study included 164 patients treated with NAC and radical nephroureterectomy (RNU) for clinically non-metastatic, high-risk UTUC. The cohort was stratified into two groups according to median age. Patients received either cisplatin-based or non-cisplatin-based chemotherapies. Pathologic responses were defined as pathologic objective response (pOR; ≤ ypT1N0) and pathologic complete response (pCR; ypT0N0). Univariable and multivariable logistic and Cox regression analyses were performed to identify predictors for pathologic response and survival outcomes. RESULTS: The cohorts' median age was 68 years with the elderly group (> 68 years) comprising 74 patients. Neoadjuvant chemotherapy included methotrexate-vinblastine-doxorubicin-cisplatin (MVAC) in 66 (40%), gemcitabine cisplatin (GC) in 66 (40%) and non-cisplatin chemotherapy in 32 patients (20%). Younger patients received more often MVAC (50% vs. 28%) while elderly received more GC (34% vs. 47%) or non-cisplatin chemotherapy (16% vs. 24%) (P = .02). Overall, pOR and pCR were similar across age groups (52% vs. 47%; P = .5 and 10% vs. 8%; P = .7). While GC and non-cisplatin chemotherapy showed a lower pCR of 5% and 3%, respectively, MVAC revealed a pCR of 17% (P = .03) and was independently associated with a higher pCR (OR 4.31; P = .03). Kaplan-Meier analysis showed no difference in recurrence-free and cancer-specific survival, whereas a lower rate was seen in overall survival for the elderly. CONCLUSION: Elderly patients with high-risk UTUC eligible for cisplatin-based NAC prior to RNU may benefit from this multimodal therapy equally as their younger counterparts. Cisplatin-ineligible patients undergoing non-cisplatin-based NAC appeared to have lower response rates and should be considered for immediate RNU.
Keywords: protokoly protinádorové kombinované chemoterapie; cisplatina; retrospektivní studie; lidé; Aged; neoadjuvantní terapie; Humans; Urinary Bladder Neoplasms; Carcinoma, Transitional Cell; Cisplatin; Antineoplastic Combined Chemotherapy Protocols; Neoadjuvant Therapy; nádory močového měchýře; senioři; karcinom z přechodných buněk; Retrospective Studies